An i*-based approach for modeling and testing web requirements - Robles Luna, Esteban
Web designers usually ignore how to model real user expectations and goals, mainly due to the large and heterogeneous audience of the Web. This fact leads to websites which are difficult to comprehend by visitors and complex to maintain by designers; these problems could be ameliorated if users are able to evaluate the application under development providing their feedback. To this aim, in this paper we present an approach for using the i* framework for modeling users' goals with mockups and WebSpec diagrams for detailing the specification of Web requirements, in such a way that the process of evaluating i* models for Web applications can be automated thus improving users' feedback during the development process. Also, as part of our development approach, we derive the domain and navigational models by defining a set of automatic transformations to a specific Web modeling method. Finally, we illustrate our approach with a case study to show its applicability and describe a prototype tool that supports the process.